2016
DOI: 10.15171/jcs.2016.021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness-integrated Cognitive Behavior Therapy on Depression and Anxiety among Pregnant Women: a Randomized Clinical Trial

Abstract: Introduction: Pregnancy can be associated with different psychological problems such as depression and anxiety. These problems are often neglected and left untreated. This study aimed to examine the effect of mindfulness-integrated cognitive behavior therapy on depression and anxiety among pregnant women. Methods: A convenient sample of 80 pregnant women were selected. Participants were randomly allocated to either the experimental or the control groups. Participants in the experimental group received mindful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 44 publications
3
80
0
3
Order By: Relevance
“…These results were congruent with the study conducted by Yazdanimehr et al [19] to determine the effect of Mindfulness integrated Cognitive Behavior Therapy on depression and anxiety among pregnant women. They studied 80 pregnant women, 40 in the experimental and 40 in the control groups.…”
Section: Discussionsupporting
confidence: 91%
“…These results were congruent with the study conducted by Yazdanimehr et al [19] to determine the effect of Mindfulness integrated Cognitive Behavior Therapy on depression and anxiety among pregnant women. They studied 80 pregnant women, 40 in the experimental and 40 in the control groups.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in compliance with the results of our study. Nevertheless, they used the Edinburg Postnatal Depression Scale and the Beck Anxiety Inventory to collect data on the study groups, therefore, their scales and the sample group were different from those of the present research (32).…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with the results of a research by Sohrabi et al (2014) in which they reported a reduction in symptoms of depression in patients with Type II diabetes mellitus following the implementation of an 8-session MiCBT program (30). Yazdanimehr et al (2016) conducted a study to determine the effect of MiCBT on depression and anxiety among pregnant women. They studied 80 pregnant women, 40 in the experimental and 40 in the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with those obtained in other studies. In a study, Yazdani Mehr and et al showed the effect of 8 sessions of cognitive–behavioral‐based mindfulness program on stress and depression in pregnant mothers (Yazdanimehr, Omidi, Sadat, & Akbari, ). The results of another 6‐session counseling showed anxiety reduction in the intervention and control group, but the anxiety reduction was reported more in the intervention group.…”
Section: Discussionmentioning
confidence: 99%